Комунікативний менеджмент в управлінні ризиками соціальної прозорості інформаційних систем підприємства - Мазник, Ліана Валеріївна; Драган, Олена Іванівна; Турчина (Побережна), Марія Петрівна (My University, 2022)
Одним із напрямків вдосконалення інструментів комунікативного менеджменту в умовах сучасних викликів є релевантне забезпечення актуальних змін у форматах організації праці. Набувають популярності дистанційна робота та змішані формати. Дистанційна робота означає використання інформаційних і комунікаційних технологій для роботи поза робочим місцем. Криза Covid-19, повномасштабна війна в Україні призвела до збільшення використання інструментів соціальних мереж на підприємствах. Напрямками їх використання є контроль, інформування, координація співпраці між працівниками. В таких умовах комунікативний менеджмент має враховувати не тільки вимоги, але й ризики соціальної прозорості. Соціальна прозорість здійснюється через соціальні мережі або корпоративне соціальне програмне забезпечення, стосується добровільного обміну особистою та контекстною інформацією, такою як інформація про їхній власний статус і статус команди, наміри, мотивацію, можливості, пріоритети, цілі, оновлення фізичної та соціальної інформації, контакти з іншими колегами. Практики соціальної прозорості можуть створити такі ризики, як перевантаження інформацією, професійне вигорання, стрес. Бракує систематичних методів комунікативного менеджменту, які б ідентифікували та оцінювали ризики соціальної прозорості. В представленому дослідженні обґрунтовується метод ідентифікації та оцінки таких ризиків на підприємствах. Розроблено відповідний алгоритм методу ідентифікаціїї та оцінки таких ризиків в організаційному контексті. One of the areas of improvement of communicative management tools in the conditions of modern challenges is the relevant provision of actual changes in the formats of work organization. Remote work and mixed formats of work are gaining popularity. Remote work means using information and communication technologies to work outside the workplace. The Covid-19 crisis and the full-scale war in Ukraine have led to an increase in the use of social media tools in enterprises. The directions of their use control, inform, and coordinate cooperation between employees. In such conditions, communicative management must consider not only the requirements but also the risks of social transparency. Social transparency is carried out through social networks or corporate social software, refers to the voluntary sharing of personal and contextual information, such as information about their own and team status, intentions, motivations, capabilities, priorities, goals, updates of physical and social information, contacts with others colleagues. Social transparency practices can create risks such as information overload, professional burnout, and stress. There is a lack of systematic communication management methods that would identify and assess the risks of social transparency. In the presented study, we substantiate the method of identification and assessment of such risks at enterprises. The most threatening risks include: high level of disclosure of personal information; distribution of personal data of employees without their consent; lack of relevant data protection in the organization; excessive dependence on information technologies; risk of breach of confidentiality; risk of financial loss. An appropriate algorithm for the method of identification and assessment of such risks in the organizational context has been developed. The use of such tools in the practical activities of enterprises will improve the validity of management decisions in the context of the transparency of corporate information systems based on the identification of relevant risks and their prioritization.
Keywords: кафедра економіки праці та менеджменту; комунікативний менеджмент; комунікації; соціальна прозорість; соціальне програмне забезпечення підприємства; інформаційні системи підприємства; ризики; communicative management; communications; social transparency; social enterprise software; enterprise information systems; risks